A new discinoid Kosoidea australis sp. nov. from the Iapó and Vila Maria Formations, NE Paraná Basin, Brazil - Zabini, Carolina; Furtado-Carvalho, Ana Beatriz; Carmo, Dermeval Do; Assine, Mário Luis [UNESP] (Taylor & Francis, 2019)
Many fossil brachiopod genera are used to comprehend previous geological settings. Such fossils often provide trustworthy information about ancient earth configurations, such as the supercontinent Gondwana. This study presents a new occurrence of a discinoid brachiopod, from the Iapó and Vila Maria Formations of the Paraná Basin. Fossiliferous strata overlie deposits of glacial and post-glacial times, here interpreted as Hirnantian in age. This is the first occurrence of Kosoidea for Paleozoic strata of Brazilian Sedimentary Basins. A new discinoid species Kosoidea australis sp. nov. is erected. Disarticulated valves are extremely abundant as juveniles in transgressive marine mudrocks. The new species is characterised by a convexo-plane shell and a marked posterior triangular pedicle opening. The microornamentation consists of pits arranged in radial rays, mostly visible on the dorsal valve surface. Adults are rare, and a size-sorting process probably sieved and fragmented the valves during transportation and fossilisation. Medium to large discinoids–such as the one here described–are commonly associated with chilly waters. The presence of this genus both in Soom Shale (Cape Basin, South Africa) and in Paraná Basin, associated to sedimentological data points to a possible connection between the two in marginal basins of Gondwana, during the Early Paleozoic. urn:lsid:zoobank.org:pub:0E35F946-051C-4DD7-AA43-23E0FFD59FF3.
Keywords: Brachiopoda; Discinidae; Gondwana; Hirnantian; taxonomy